Alleviation of enzymatic browning and maintenance of postharvest quality of litchi (Litchi chinensis) fruit with packaging films - SHILPA, SHILPA; MAHAJAN, B V C; SINGH, NAVPREM; SHARMA, SUCHETA; KAUR, SUMANJIT (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out during the years 2016–17 and 2017–18 to evaluate the effect of different packaging films for control of pericarp browning and maintenance of postharvest quality of litchi (Litchi chinensis Sonn.) fruits during cold storage. Litchi fruits of cultivar Dehradun were harvested at physiological mature stage and de-stalked. The fruits were packed in low density polyethylene film (LDPE, 25 μ), high density polyethylene film (HDPE, 10 μ) and heat shrinkable film (15 μ). The control fruits were packed with in gunny sack with litchi leaves as per traditional technique.The fruits were then stored in walk-in-cold store (2-3°C and 90-95% RH) for 4 weeks. The results revealed that LDPE packaging film proved to be the most effective in minimizing the pericarp browning of litchi fruits. LDPE film resulted in reducing the weight loss, browning index and maintained, organoleptic quality, TSS, acidity, ascorbic acid and gave the best browning inhibition during the storage by reducing the activities of polyphenol oxidase and maintained a higher level of total anthocyanin. The data revealed that litchi fruits packed in LDPE films can be stored successfully up to three weeks with acceptable marketable quality.